2020
DOI: 10.1002/jum.15592
|View full text |Cite
|
Sign up to set email alerts
|

Concordance Between Obstetric Anatomic Ultrasound and Fetal Echocardiography in Detecting Congenital Heart Disease in High‐risk Pregnancies

Abstract: Objectives To evaluate the concordance between second‐trimester anatomic ultrasound and fetal echocardiography in detecting minor and critical congenital heart disease in pregnancies meeting American Heart Association criteria. Methods We conducted a retrospective cohort study of pregnancies in which a second‐trimester fetal anatomic ultrasound examination (18–26 weeks) and fetal echocardiography were performed between 2012 and 2018 at our institution based on American Heart Association recommendations. Anatom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
2
0
1
Order By: Relevance
“…These previous studies have noted an approximately 2–3% missed CHD diagnosis rate on the second-trimester screening ultrasound when compared to an F-echo in the current era [ 13 , 18 ]. The possibility of a missed critical CHD when there was a prior normal second-trimester screening ultrasound was < 0.5% in large population studies [ 13 , 19 , 20 ]. The estimated number of F-echo needed to be performed to detect a missed critical CHD ranged from 249 to 750 [ 13 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…These previous studies have noted an approximately 2–3% missed CHD diagnosis rate on the second-trimester screening ultrasound when compared to an F-echo in the current era [ 13 , 18 ]. The possibility of a missed critical CHD when there was a prior normal second-trimester screening ultrasound was < 0.5% in large population studies [ 13 , 19 , 20 ]. The estimated number of F-echo needed to be performed to detect a missed critical CHD ranged from 249 to 750 [ 13 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…(Bravo-Valenzuela et al, 2018) Because of the restricted fetal position and limited amniotic fluid, late gestation imaging is more difficult. This explains why it is critical to identify and refer suspected abnormalities as soon as possible [24]. Mamalis et al found that double outlet right ventricle and right heart anomalies had slightly lower diagnosis accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…В то же время в соответствии с текущими рекомендациями по скринингу Американской кардиологической ассоциации автоматическая эхокардиография в период внутриутробного развития при визуализированных нормальных характеристиках сердца приносит ограниченную пользу в выявлении врожденных пороков сердца, требующих немедленных послеродовых вмешательств. Исследователи отмечают, что следует изучить возможность более избирательного использования автоматической эхокардиографии плода в условиях повышенного риска ВПС [19].…”
Section: интерпретация результатов ультразвукового исследованияunclassified